A model for monitoring the process of forming professional competence of future special education teachers - Strelnikov, V. (Problems of Engineer-Pedagogical Education, 2021)
The article highlights the theoretically substantiated and developed model for monitoring the process of forming professional competence of future special education teachers in Poltava National Pedagogical University named after V.H. Korolenko (taking into account international standards ISO 9001:2015) and also evaluates its effectiveness. Professional training of future teachers of special education is considered to be a purposeful guided process that ensures the formation of professional competence necessary for the implementation of their professional activities. The components of professional competence of a special education teacher that should be taken into account when assessing the quality of their activities include motivational, cognitive, affective and conative components, pedagogical abilities and professional personal qualities. The result of the author's model of monitoring the process of forming professional competence of future special education teachers consists in the outlined ways to implement the structural elements of this model, which include purpose, content, technology and structure of the training system, teaching principles, pedagogical skills of teachers. This process was monitored according to a two-dimensional matrix model whose elements included contracts analysis; management of design, documents and students’ preparation; identification and tracking; management of processes, control and students who fall behind; forms and methods of keeping documents; internal quality audit; training of teaching professionals who instruct future teachers of special education; service; statistical methods. Its components included the quality of the result, content, technology, evaluation, organization, and staff. It is promising to further determine the optimal characteristics of professional competence of future special education teachers in social (when considering the requirements of society to this phenomenon) and structural aspects (when this competence is a set of interdependent elements with given characteristics).